Improving the Mechanisms for Developing Future Teachers’ Motivation to Organize Educational Activities of Students - Odilova Makhfuza (Researchparks Publishing, 2026)
This article analyzes the theoretical-methodological foundations, pedagogical conditions and practical mechanisms of developing the motivation of students to organize educational activities among future teachers. Also, the role of innovative pedagogical technologies, digital learning environment, reflection and pedagogical practice in the formation of professional motivation is scientifically based. Based on the research results, a conceptual model of motivation development is proposed.